ON-THE-JOB TRAINING IN COFFEEHOUSE CHAINS EMPLOYEES- A NEW TREND OR A PREREQUISITE? - Agagiotou, Smaro (PEOPLE: International Journal of Social Sciences, 2020)
The present study examines the relationship between coffeehouse chains employees’ on-the-job training and their productivity, as factors that may have contributed to the sector’s development during the economic crisis in Greece. The reason for conducting this research was the development and expansion of training for employees in coffeehouse chains as an HR practice. This is quantitative research, with a sample consisted of 175 coffeehouse chain employees in Thessaloniki, Greece. The required data were collected using Job Training and Job Satisfaction Survey (only the part related to job training) developed by Schmidt (2004) and Job Performance Scale developed by Williams and Anderson (1991). The results of this study showed that there is a significant and positive relationship between the sample’s on-the-job training and their productivity and thus, this training constitutes a predictive factor for the employees’ productivity. Findings also revealed that women and older employees in coffeehouse chains evaluated training as more important than men and younger employees. Similar results were observed with respect to the relationship between age and productivity, as younger employees had lower productivity. This research contributes to the relevant field by highlighting the impact of training on employee productivity. As the coffeehouse industry is a crucial sector for the Greek economy, further studies on the job’s characteristics and employees’ well-being should be conducted.